1986
DOI: 10.1084/jem.164.4.1179
|View full text |Cite
|
Sign up to set email alerts
|

T cell suppressors of antitumor immunity. The production of Ly-1-,2+ suppressors of delayed sensitivity precedes the production of suppressors of protective immunity.

Abstract: A central problem in tumor immunology has been to explain how immunogenic tumors escape destruction by the immune defenses of their immunocompetent hosts. The results of studies performed during the past few years in this laboratory (reviewed in 1) support the hypothesis that certain tumors with tumorspecific, transplantation antigens avoid destruction by the immune response of their hosts by evoking the production of a population of suppressor T cells that functions to downregulate the immune response before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Because the majority of solid tumors are thought to express tumor-associated Ags (TAA), 2 it is believed that the induction of an effective anti-TAA immune response may enable the eradication of micrometastases. Studies in experimental models have indicated that TAA on many tumors are "concealed" from the immune system by two major mechanisms: 1) the tumor microenvironment and local cytokine milieu that often suppress immune function and may actively induce immune cell tolerance, anergy, and death (1-4); and 2) regulatory T cells (Treg) within the tumor and/or in the circulation that suppress the development of an anti-TAA (i.e., anti-tumor) immune response (5)(6)(7)(8).…”
Section: Intratumoral Injection Of ␣-Gal Glycolipids Induces Xenografmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the majority of solid tumors are thought to express tumor-associated Ags (TAA), 2 it is believed that the induction of an effective anti-TAA immune response may enable the eradication of micrometastases. Studies in experimental models have indicated that TAA on many tumors are "concealed" from the immune system by two major mechanisms: 1) the tumor microenvironment and local cytokine milieu that often suppress immune function and may actively induce immune cell tolerance, anergy, and death (1-4); and 2) regulatory T cells (Treg) within the tumor and/or in the circulation that suppress the development of an anti-TAA (i.e., anti-tumor) immune response (5)(6)(7)(8).…”
Section: Intratumoral Injection Of ␣-Gal Glycolipids Induces Xenografmentioning
confidence: 99%
“…These APC transport internalized TAA to draining lymph nodes where they present TAA peptides for the activation of tumor-specific cytotoxic and helper T cells at levels sufficient to overcome suppressive Treg activity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We have developed a novel method for achieving immune-mediated destruction of tumor lesions, recruitment of APC into the lesions, effective intratumoral targeting of TAA to recruited APC, and induction of a protective anti-tumor immune response by exploiting the naturally produced anti-Gal Ab.…”
Section: Intratumoral Injection Of ␣-Gal Glycolipids Induces Xenografmentioning
confidence: 99%
“…This phenomenon has been deemed a mechanism for tumor metastasis (4 -6). In a series of elegant studies, it was proposed that concomitant tumor immunity represents a balance between tumor-induced CD8 effectors and suppressor T cells (7,8). However, after this proposal, there was no progress made in the area for two decades, as the existence of suppressor cells was in doubt.…”
mentioning
confidence: 99%
“…Cytokines such as IL-7 and IL-21 are key molecules that provide necessary signals for T-cell proliferation [115,116]. LDCy may also enhance immune responses by preferentially targeting CD4 + regulatory T-cells, which have been shown to be inhibitory towards CTL and HTL responses against self-antigens such as TAA [117][118][119][120][121][122][123].…”
Section: Vaccine Adjuvantsmentioning
confidence: 99%